KONSTRUKSI GENDER DALAM NASKAH WA'ASYIRUHUNNA BIL MA‘RUF - Herliana, Rina; Ma'mun, Titin Nurhayati; Ikhwan, Ikhwan (Arabi : Journal of Arabic Studies, 2019)
Manuscript Wa'asyiruhunna bil Ma'ruf contains advices to husband and wife in a household. This advices manuscript has a Nadhom form with an Arabic format of poem. The uniqueness of this manuscript is that it contains a gender construction in dividing the role of husband and wife in Islamic view at the year 1956, the time when this manuscript had been written. This can be a solution for patriarchal culture's view that tends to have a subordinate and oppressive attitude towards women. One impact from this attitude is the emergence of feminisms and the issue of gender equity. This manuscript will indirectly reveal some views on feminisms, whether the gender construction described is considered fair or not. The scope of gender construction discussed in this manuscript is departing from the bond of husband and wife in the household. Through qualitative, descriptive and analytical research method for this text, it is hoped that an Islamic concept of gender equity will be formed, an understanding of women's rights can be a consideration in the formation of a happy and harmonious family and his relation to feminisms.